(untitled) (Fiep Bulletin - online, 2014)
For the creation’s sake of a praxic human! This article is part of a PhD thesis. It´s a qualitative study, compromised with the Human Motricity Science and also with a creation of an education as a social and cultural project, as a pedagogic-political project and above all as an anthropologic project that views the excellence of the humane condition, toward to a creative and emancipative praxic. Based on the fundamentals and presupposition of the Human Motricity Science, under the protection of the unit and complexity’s paradigm, we focused on the human being viewing to the educative process, looking forward an emancipated individual and an agent of his/her own life ( a praxic being ). A transforming education is workable, because through it, we can contribute for human being to learn how to know, to do, to live with each other and to be.